Impaired Stomatal Control Is Associated with Reduced Photosynthetic Physiology in Crop Species Grown at Elevated [CO2] - Haworth, Matthew; Killi, Dilek; Materassi, Alessandro; Raschi, Antonio; Centritto, Mauro (Frontiers in Plant Science, 2016)
Physiological control of stomatal conductance (Gs) permits plants to balance CO2-uptake for photosynthesis (PN) against water-loss, so optimising water use efficiency (WUE). An increase in the atmospheric concentration of carbon dioxide ([CO2]) will result in a stimulation of PN and reduction of Gs in many plants, enhancing carbon gain while reducing water-loss. It has also been hypothesised that the increase in WUE associated with lower Gs at elevated [CO2] would reduce the negative impacts of drought on many crops. Despite the large number of CO2-enrichment studies to date, there is relatively little information regarding the effect of elevated [CO2] on stomatal control. Five crop species with active physiological stomatal behaviour were grown at ambient (400 ppm) and elevated (2000 ppm) [CO2]. We investigated the relationship between stomatal function, stomatal size and photosynthetic capacity in the five species, and then assessed the mechanistic effect of elevated [CO2] on photosynthetic physiology, stomatal sensitivity to [CO2] and the effectiveness of stomatal closure to darkness. We observed positive relationships between the speed of stomatal response and the maximum rates of PN and Gs sustained by the plants; indicative of close co-ordination of stomatal behaviour and PN. In contrast to previous studies we did not observe a negative relationship between speed of stomatal response and stomatal size. The sensitivity of stomata to [CO2] declined with the ribulose-1,5-bisphosphate limited rate of PN at elevated [CO2]. The effectiveness of stomatal closure was also impaired at high [CO2]. Growth at elevated [CO2] did not affect the performance of photosystem II indicating that high [CO2] had not induced damage to the photosynthetic physiology, and suggesting that photosynthetic control of Gs is either directly impaired at high [CO2], sensing/signalling of environmental change is disrupted or elevated [CO2] causes some physical effect that constrains stomatal opening/closing. This study indicates that while elevated [CO2] may improve the WUE of crops under normal growth conditions, impaired stomatal control may increase the vulnerability of plants to water deficit and high temperatures.